PSYCHOLOGICAL CONFLICTS BETWEEN KEY CHARACTERS IN GILLIAN FLYNN’S GONE GIRL - Amalia, Suci; Barus, Efendi; Pawiro, Muhammad Ali (JOURNAL OF LANGUAGE, 2025)
Gone Girl, a novel by Gillian Flynn, explores the intense psychological and emotional conflict between a married couple, Amy and Nick Dunne. Amy desires love and loyalty but is devastated by Nick’s betrayal. Meanwhile, Nick, who is obsessed with emulating his father, fails to express love to Amy and instead engages in an affair, leading to suspicion when Amy suddenly disappears. Amy’s uncontrollable ego drives her to fake her own death and frame Nick for murder as a form of social punishment. The story unfolds through public suspicion, legal investigation, and emotional turmoil. This study applies Cascio’s theory of conflict to examine the types and dynamics of internal and external conflicts experienced by the main characters. The study also aims to identify the negative impacts resulting from these conflicts. Using a qualitative descriptive method, the research analyzes how internal conflict (man versus self) and external conflict (man versus man, society, and fate) shape the narrative. Amy’s psychological need for validation and her manipulative actions lead her to deep guilt and emotional suffering. Nick, on the other hand, experiences social rejection, emotional stress, and job loss after being falsely accused. These conflicts result in significant behavioral changes and deteriorating mental, physical, and social well-being. The novel reveals how unresolved personal and relational conflicts can escalate into destructive outcomes.